Pendekatan Permintaan dan Penawaran untuk Analisis Kebijakan Perberasan di Indonesia - Endang Siti Rahayu (Caraka Tani: Journal of Sustainable Agriculture, 2007)
Productivity of the rice on Indonesia to depend of the more variables. Its variables include rice productivity on the farmer, the supply and demand prices, production cost, the farmers salary and the government policy. That are variables have to the effect on the increasing of the rice production and than to mullyflyer effect of the development acelrelation on the all aspect